Coping with drought in Tamil Nadu: The role of reservoir management - Rajagopalan, V.; Swaminathan, P. (International Food Policy Research Institute, 1990)
Indian agriculture has historically been vulnerable to floods and droughts, primarily associated with the monsoon. These extreme weather events have retarded the otherwise impressive progress India has made in agricultural production, particularly during the past two decades. Food security, based on adequate buffer stocks of foodgrains, is often threatened. For example, the drought of 1987-88 reduced the aggregate output of foodgrains to between 135 and 140 million tons, far below the expected output of between 157 and 162 million tons for normal and well-distributed rainfall. Buffer stocks were badly depleted. Increasing food security and the stability of annual output levels in the face of variable rainfall has again emerged as a major concern of planners. To eliminate the threat of a food crisis comparable to that of the early sixties, effective management strategies must be identified.